A kind of low solvent residue UV transfer paper and preparation method thereof
By adding aqueous ultraviolet absorber to the varnish of UV transfer paper, the photoinitiator fission is prevented, and the problem of excessive solvent residue in UV transfer paper is solved, achieving the effect of meeting the cigarette pack standards and improving fastness.
Patent Information
- Application Number
- CN202311273023.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-09-28
AI Technical Summary
During the ultraviolet curing process of existing UV transfer paper, the content of organic solvents acetone and benzene often exceeds the standard, which seriously does not meet the requirements of the solvent residue in cigarettes.
After the UV coating is cured and when UV light is passed again, the fission of the photoinitiator in the coating is prevented by adding an aqueous ultraviolet absorber to the varnish, thereby reducing solvent residue.
It effectively reduces the solvent residue, makes the product meet the smoking-pack solvent residue standards, and at the same time improves the fastness and binding force of UV transfer paper under high temperature and high humidity conditions.
Smart Images

Figure CN117188209B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to low-solvent residual UV transfer paper and a preparation method thereof, and belongs to the technical field of cigarette packaging materials. Background Art
[0002] In the early stage of cigarette packaging products, aluminum-sprayed transfer cardboard and laser aluminum-sprayed transfer cardboard were the main products, and they have been used for many years. With the continuous upgrading of products, various companies hope that the packaging of their products can have a novel appearance that quickly attracts consumers' attention. Existing anti-counterfeiting methods are constantly being innovated. Deep-grained optical patterns such as Fresnel lenses, metal three-dimensional reliefs, color light lenses, white light lenses, etc. are being increasingly used in the packaging field because of their excellent 3D changes and novel dynamic effects. Because the depth of deep-grained optical patterns can reach 5-15μm, it cannot be achieved by traditional hot pressing methods. UV transfer products came into being. After ultraviolet curing, the content of organic solvents acetone and benzene in the micro-nano structure UV transfer paper often exceeds the standard, and the subsequent UV printing is cured again by ultraviolet light, which makes the content of organic solvents acetone and benzene exceed the standard seriously, which seriously does not meet the standard requirements for solvent residues in cigarette packaging.
[0003] Therefore, the problem of excessive solvent residues needs to be solved. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies in the prior art and provide a low solvent residue micro-nano structure medium UV transfer paper and its preparation method. The acetone and benzene produced by the fission of the photoinitiator in the UV coating, so this patent needs to prevent the fission of the photoinitiator in the coating when it is subjected to ultraviolet light again after the UV coating is cured. Because the surface tension of the UV coating is small, it is generally necessary to apply varnish before printing. A water-based ultraviolet absorber is added to the varnish. When the ultraviolet light or UV printing is cured again, the varnish layer effectively blocks the ultraviolet rays from reaching the UV coating, thereby failing to trigger the fission of the photoinitiator, so that the product has a small solvent residue and meets the standard for solvent residues in cigarette packages.
[0005] In order to achieve the above object, the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a low-solvent residual UV transfer paper, comprising a back coating, a base paper layer, a water-based environmentally friendly adhesive layer, a dielectric layer, a water-based bonding coating, a UV transfer coating, and a water-based paint layer containing a water-based ultraviolet absorber.
[0007] The back coating layer, the base paper layer, the water-based environmentally friendly adhesive layer, the dielectric layer, the water-based bonding coating layer, the UV transfer coating layer, and the water-based paint layer are sequentially compounded into one body, and the surface of the UV transfer coating layer close to the water-based bonding coating layer has a micro-nano structure;
[0008] The water-based paint layer adopts water-based acrylic varnish and adds 5-10% of water-based ultraviolet absorber to the total weight of the water-based acrylic varnish.
[0009] Preferably, the back coating layer is made of acrylic emulsion with a solid content of 8-15%, a softening point of 105-120°C, an acid value of 7-10 mg KOH / g, and a dry coating amount of 0.5-0.7 g / m 2 .
[0010] Preferably, the water-based environmentally friendly adhesive layer adopts a water-based environmentally friendly acrylic polymer transfer glue; the transfer glue particle diameter is 0.14 microns, the solid content is 43±2%, the pH value is 5.0-7.0, the viscosity measured at a temperature of 25°C is 40-50 seconds, and the coating amount is 5-8g / m 2 .
[0011] Preferably, the dielectric layer is a transparent dielectric layer or a metal dielectric layer.
[0012] Preferably, the dielectric layer is a zinc sulfide dielectric layer, and the zinc sulfide dielectric layer uses block zinc sulfide. The block zinc sulfide is heated at high temperature and vaporized by vacuum aluminum plating equipment, and then cooled and deposited on the surface of the aqueous bonding coating to form a zinc sulfide highlight layer. The transmittance represented by the thickness of the zinc sulfide is 64-66%.
[0013] Preferably, the water-based bonding coating is made of water-based polyurethane, water-based acrylic resin or a mixture thereof, the solid content of the water-based bonding coating is 8-15%, and the dry coating amount is 0.3-0.6 g / m 2 The thickness of the water-based binding coating is 1 to 3 μm, and the surface shape of the water-based binding coating is consistent with the micro-nano structure of the UV transfer coating.
[0014] Preferably, the UV transfer coating is made of UV light-cured acrylic monomer coating, and the cross-section of the micro-nano structure on the surface of the UV transfer coating is one or a combination of arc, square, triangle, trapezoid, and step shapes.
[0015] In a second aspect, the present invention provides a method for preparing low solvent residual UV transfer paper, characterized in that the method is as follows:
[0016] Step 1: a deep-grained three-dimensional relief laser graphic holographic master is produced on the same holographic plate by changing the width and angle of the interference fringes and using local focus arc walking position photolithography;
[0017] Step 2: Apply UV transfer coating on the surface of the base film layer, and simultaneously perform molding with a plate roller with a deep-grained three-dimensional embossed laser graphic holographic master, use LED ultraviolet lamp for oxygen-free curing, oven heating, and the mesh number of the anilox roller is N; obtain a UV transfer coating with a micro-nano structure laser pattern;
[0018] Step 3, coating a water-based bonding coating on the UV transfer coating with the micro-nano structure laser pattern, the mesh number of the anilox roller is M, M is greater than N, and the oven temperature is set to first increase in steps and then decrease in steps;
[0019] Step 4, corona treatment of the surface of the water-based bonding coating;
[0020] Step 5, coating a dielectric layer on the surface of the water-based bonding coating;
[0021] Step 6: On a precision positioning laminating machine, the back of the base paper layer is back-coated with acrylic emulsion to form a back coating layer, and the front of the base paper layer is laminated with the medium layer of the laser holographic pattern. After the lamination, the base film layer is peeled off online, and at the same time, a water-based varnish layer with a water-based ultraviolet absorber is coated by an anilox roller, and the mesh number of the coating anilox roller is M;
[0022] Step seven, positioning the width and plate spacing required for slitting on the positioning sheeting machine to form a low solvent residue micro-nano structure medium UV transfer paper.
[0023] Specifically, the method is as follows:
[0024] Step 1: a deep-grained three-dimensional relief laser graphic holographic master is produced on the same holographic plate by changing the width and angle of the interference fringes and using local focus arc walking position photolithography;
[0025] Step 2: Apply UV transfer coating on the surface of the base film layer at a coating speed of 20-50m / min on a UV positioning laser machine, and at the same time, mold it with a plate roller with a deep-grained three-dimensional embossed laser graphic holographic master. Use LED ultraviolet lamp for oxygen-free curing. The oven temperature is controlled at 70℃ and 80℃ in turn. The anilox roller is a 120-mesh electric engraving steel roller, and the coating amount is 7.0-10.0g / m 2 ; Obtaining a UV transfer coating with a micro-nano structure laser pattern;
[0026] Step 3, coating a water-based bonding coating on the UV transfer coating with a micro-nano structure laser pattern, the anilox roller is 250 mesh, the speed is 100-120 m / min, and the oven setting temperature is 80°C-130°C-150°C-140°C-120°C;
[0027] Step 4, performing corona on the surface of the water-based bonding coating at a speed of 100-120 m / min on a corona machine, and the corona power is 4-7 KW;
[0028] Step 5, coating a dielectric layer on the surface of the water-based bonding coating, wherein the dielectric layer has a transmittance of 64-66%;
[0029] Step 6: On a precision positioning laminating machine, the back of the base paper layer is back-coated with acrylic emulsion to form a back coating layer, and the front of the base paper layer is laminated with the medium layer of the laser holographic pattern. After the lamination, the base film layer is peeled off online, and at the same time, a water-based varnish layer with a water-based ultraviolet absorber is coated with an anilox roller with a thickness of 2-4um and a coating anilox roller of 250 mesh;
[0030] Step seven, positioning the width and plate spacing required for slitting on the positioning sheeting machine to form a low solvent residue micro-nano structure medium UV transfer paper.
[0031] Preferably, in step five, the specific operation is: using a vacuum aluminum plating machine to coat the block zinc sulfide at 10 -2 ~10 -3 Under the vacuum condition of 1.3 Pa, it is heated to 1400℃ and vaporized, and then attached to the surface of the aqueous bonding coating after cooling to form a zinc sulfide dielectric layer with a laser holographic pattern.
[0032] The present invention has the following beneficial effects: (1) The present invention applies a varnish with a water-based ultraviolet absorber before printing. When ultraviolet light is irradiated or UV printing is cured again, the varnish layer effectively blocks the ultraviolet light from reaching the UV coating, thereby failing to induce fission of the photoinitiator, so that the product has a smaller solvent residue, which meets the solvent residue standard of cigarette packages.
[0033] (2) UV medium transfer paper currently has the problem of poor UV coating bonding, especially under high temperature and high humidity conditions, the UV coating will easily fall off the medium layer. The present invention not only solves the problem of solvent residue, but also adds a bonding coating, so that the UV transfer coating and the zinc sulfide medium layer can be effectively and firmly bonded, and the coating will not fall off under high temperature and high humidity conditions.
[0034] (3) The UV transfer paper of the present invention has low solvent residue, which meets the requirements of cigarette packaging products. The water-based coating and UV transfer coating are 100% solid, zero emission, and environmentally friendly; the deep-grained three-dimensional structure has a beautiful appearance; and the fastness problem of the existing medium UV transfer coating is overcome. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the structure of a low solvent residue UV transfer paper;
[0036] Figure 2 Schematic diagram of the state of base film peeling off. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0038] A low-solvent-residue UV transfer paper comprises a back coating 1, a base paper layer 2, a water-based environmentally friendly adhesive layer 3, a zinc sulfide medium layer 4, a water-based bonding coating 5, a UV transfer coating 6 with a micro-nanostructure laser pattern, and a water-based paint layer 7 containing a water-based ultraviolet absorber.
[0039] The back coating layer 1, the base paper layer 2, the water-based environmentally friendly adhesive layer 3, the dielectric layer 4, the water-based bonding coating layer 5, the UV transfer coating layer 6 having a micro-nano structure laser pattern, and the water-based paint layer 7 having a water-based ultraviolet absorber are composited into one in sequence; the surface of the UV transfer coating 6 away from the base film layer 8 has a micro-nano structure, the surface shape of the water-based bonding coating 5 is consistent with the micro-nano structure of the UV transfer coating 6, and the surface shape of the dielectric layer 4 is also consistent with the micro-nano structure of the UV transfer coating 6.
[0040] The back coating 1 is made of acrylic emulsion with a solid content of 8-15%, a softening point of 105-120°C, an acid value of 7-10 mg KOH / g, and a dry coating amount of 0.5-0.7 g / m 2 .
[0041] The water-based environmentally friendly adhesive layer 3 adopts a water-based environmentally friendly acrylic polymer transfer glue; the transfer glue particle diameter is 0.14 microns, the solid content is 43±2%, the pH value is 5.0-7.0, the viscosity measured under the conditions of No. 4 cup coating (4 cup coating detection, 4 viscometer coating) and temperature of 25°C is 40-50 seconds, and the coating amount is 5-8g / m 2 .
[0042] The dielectric layer 4 is a transparent dielectric layer or a metal dielectric layer. The transparent dielectric layer can be made of zinc sulfide or magnesium fluoride. Specifically, block zinc sulfide is used. The block zinc sulfide is heated at high temperature and vaporized by vacuum aluminum plating equipment, and then cooled and deposited on the surface of the aqueous bonding coating 5 to form a zinc sulfide highlight layer. The thickness of the zinc sulfide represents a transmittance of 64 to 66%.
[0043] Water-based bonding coating 5 This layer uses water-based polyurethane, water-based acrylic resin or a mixture thereof. The solid content of the water-based bonding coating is 8-15%, and the dry coating amount is 0.3-0.6 g / m 2 , with a thickness of 1 to 3 um; the water-based bonding coating can effectively combine well with the UV coating and the dielectric layer.
[0044] The UV transfer coating 6 with a micro-nano structure laser pattern adopts UV light-cured acrylic monomer coating, and is coated with a molded holographic pattern. Laser anti-counterfeiting information including lenses and reliefs can be molded, and the depth of the laser information stripes ranges from 0.5 to 5 μm. The cross-section of the micro-nano structure on the surface of the UV transfer coating 6 is one or a combination of arc, square, triangle, trapezoid, and step shapes. The surface shapes of the water-based bonding coating 5 and the dielectric layer 4 are consistent with the micro-nano structure of the UV transfer coating 6, which is a conformal setting.
[0045] The water-based paint layer 7 with water-based UV absorber adopts water-based acrylic varnish and adds 5-10% water-based UV absorber of the total mass of water-based acrylic varnish, which can effectively absorb ultraviolet rays and prevent ultraviolet light from fissioning with the photoinitiator in the UV transfer coating. The water-based UV absorber can be selected from UV-531 and UV-5411.
[0046] The base film layer 8 is made of transfer-grade BOPET film with a thickness of 12 to 18 μm.
[0047] Example 1
[0048] A method for preparing low solvent residual UV transfer paper, the method is as follows:
[0049] Step 1: a deep-grained three-dimensional relief laser graphic holographic master is produced on the same holographic plate by changing the width and angle of the interference fringes and using local focus arc walking position photolithography;
[0050] Step 2: The base film layer 8 is made of a 13.8 μm thick BOPET film. A UV transfer coating is applied on the surface of the BOPET film at a coating speed of 20 to 50 m / min on a UV positioning laser machine. At the same time, it is molded with a plate roller with a deep-grained three-dimensional embossed laser graphic holographic working plate. LED ultraviolet lamp is used for oxygen-free curing. The oven temperature is controlled at 70°C and 80°C in turn. The anilox roller is a 120-mesh electric engraving steel roller, and the coating amount is 7.0-10.0 g / m 2 ; A UV transfer coating 6 with a micro-nano structure laser pattern is obtained; the plate roller is cylindrical, and the deep-grained three-dimensional embossed laser graphic holographic working plate is a flexible plate, which needs to be attached to the outer periphery of the plate roller and molded as a whole; the UV transfer coating is applied to the base film, and the plates are placed under the plate roller for molding, and the structure on the plate roller will be transferred to the surface of the UV coating, and the base film layer will not change;
[0051] Step 3: Apply water-based bonding coating 5 on the UV transfer coating of the molded deep-grained three-dimensional embossed laser holographic master on a coating machine, with an anilox roller of 250 mesh, a speed of 100-120 m / min, and an oven temperature of 80°C-130°C-150°C-140°C-120°C;
[0052] Step 4, performing corona on the surface of the water-based binder coating 5 at a speed of 100-120 m / min on a corona machine, and the corona power is 4-7 KW;
[0053] Step 5: Use a vacuum aluminum plating machine to coat the block zinc sulfide at 10 -2 ~10 -3Pa vacuum conditions, heated to 1400 ° C gasification, and then cooled to adhere to the surface of the water-based bonding coating 5, forming a zinc sulfide dielectric layer 4 with a laser holographic pattern, the thickness of the zinc sulfide characterization transmittance is 64-66%;
[0054] Step 6: On a precision positioning laminating machine, the back of the base paper layer 2 is back-coated with acrylic emulsion to form a back coating layer 1, and the front of the base paper layer 2 is compounded with the zinc sulfide medium layer 4 of the laser holographic pattern. After compounding, the base film layer 8 is peeled off online, and at the same time, a water-based varnish layer 7 with a water-based ultraviolet absorber is coated by an anilox roller with a thickness of 2-4um and a coating anilox roller of 250 mesh; wherein the water-based acrylic varnish is added with 5% water-based ultraviolet absorber;
[0055] Step seven, positioning the width and plate spacing required for slitting on the positioning sheeting machine to form a low solvent residue micro-nano structure medium UV transfer paper.
[0056] Example 2
[0057] Compared with Example 1, in step six, 8% of water-based ultraviolet absorber is added to the water-based acrylic varnish.
[0058] Comparative Example 1
[0059] Compared with Example 1, in step six, no water-based ultraviolet absorber is added to the water-based acrylic varnish.
[0060] Comparative Example 2
[0061] Compared with Example 1, in step six, 3% of water-based ultraviolet absorber is added to the water-based acrylic varnish.
[0062] The following detection method is used: the front side of the sample sheet 22cm*5cm is irradiated with a UV lamp with a power of 150mJ / cm2 for 3 times, each time for 15 seconds, and then the headspace-gas chromatography / mass spectrometry method standard of YC / T 207-2014 is used to detect the residual solvent in cigarette paper. The detection results of Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Table 1;
[0063] Table 1 Test results
[0064]
[0065]
[0066] From the above test data, it can be seen that adding 5-10% of water-based UV absorber to water-based acrylic varnish can reduce the content of organic solvents acetone and benzene. When the addition amount of water-based UV absorber exceeds 10%, the adaptability and selectivity of UV transfer paper in subsequent printing decrease.
[0067] Adhesive tape was used to adhere to the surfaces of Examples 1 and 2 and Comparative Examples 1 and 2, respectively, and then the tape was torn off. The surfaces of Examples 1 and 2 remained unchanged, while the patterns in the areas on the surfaces of Comparative Examples 1 and 2 were removed along with the tape. The above test shows that the bonding strength between the layers is greatly improved after adding the water-based bonding coating.
[0068] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A method for preparing low solvent residual UV transfer paper, characterized in that: The method is as follows: Step 1: a deep-grained three-dimensional relief laser graphic holographic master is produced on the same holographic plate by changing the width and angle of the interference fringes and using local focus arc walking position photolithography; Step 2: coating the surface of the base film layer (8) with a UV transfer coating (6), and simultaneously performing molding with a plate roller with a deep-grained three-dimensional embossed laser graphic holographic master, using an LED ultraviolet lamp for oxygen-free curing, oven heating, and an anilox roller with a mesh number of N; A UV transfer coating with a micro-nanostructure laser pattern is obtained; Step 3: coating a water-based bonding coating (5) on the UV transfer coating with the micro-nano structure laser pattern, the mesh number of the anilox roller is M, M is greater than N, and the oven temperature is set to first increase in steps and then decrease in steps; Step 4, corona treatment is performed on the surface of the water-based bonding coating (5); Step 5, coating the dielectric layer (4) on the surface of the water-based binding coating (5); Step 6: On a precision positioning laminating machine, the back of the base paper layer (2) is back-coated with an acrylic emulsion to form a back coating layer (1), and the front of the base paper layer (2) is laminated with the medium layer of the laser holographic pattern. After the lamination, the base film layer (8) is peeled off online, and at the same time, a water-based varnish layer with a water-based ultraviolet absorber is coated by an anilox roller, and the mesh number of the coating anilox roller is M; Step seven, positioning the width and plate spacing required for slitting on the positioning sheeting machine to form a low solvent residue micro-nano structure medium UV transfer paper.
2. The method for preparing low solvent residual UV transfer paper according to claim 1, characterized in that: The method is specifically as follows: Step 1: a deep-grained three-dimensional relief laser graphic holographic master is produced on the same holographic plate by changing the width and angle of the interference fringes and using local focus arc walking position photolithography; Step 2: Apply UV transfer coating (6) on the surface of the base film layer (8) at a coating speed of 20-50 m / min on a UV positioning laser machine, and simultaneously perform molding with a plate roller with a deep-grained three-dimensional embossed laser graphic holographic master, and use LED ultraviolet lamp for oxygen-free curing. The oven temperature is controlled at 70°C and 80°C in turn. The anilox roller is a 120-mesh electric engraving steel roller, and the coating amount is 7.0-10.0 g / m 2 ; A UV transfer coating with a micro-nanostructure laser pattern is obtained; Step 3, coating a water-based bonding coating (5) on the UV transfer coating with the micro-nano structure laser pattern, the anilox roller is 250 mesh, the speed is 100-120 m / min, and the oven setting temperature is 80°C-130°C-150°C-140°C-120°C in sequence; Step 4, performing corona treatment on the surface of the water-based binder coating (5) at a speed of 100-120 m / min on a corona machine, with a corona power of 4-7 kW; Step 5: coating a dielectric layer (4) on the surface of the water-based bonding coating (5), wherein the dielectric layer has a transmittance of 64-66%; Step 6: On a precision positioning laminating machine, the back of the base paper layer (2) is back-coated with an acrylic emulsion to form a back coating layer (1), and the front of the base paper layer (2) is laminated with the medium layer of the laser holographic pattern. After the lamination, the base film layer (8) is peeled off online, and at the same time, a water-based varnish layer with a water-based ultraviolet absorber is coated with a 2-4 um thick anilox roller, and the coating anilox roller is 250 mesh; Step seven, positioning the width and plate spacing required for slitting on the positioning sheeting machine to form a low solvent residue micro-nano structure medium UV transfer paper.
3. The method for preparing low solvent residual UV transfer paper according to claim 1, characterized in that, In step 5, the specific operation is: using a vacuum aluminum plating machine to coat the block zinc sulfide at 10 -2 ~10 -3 Under the vacuum condition of 1.3 Pa, it is heated to 1400℃ and vaporized, and then attached to the surface of the aqueous bonding coating after cooling to form a zinc sulfide dielectric layer with a laser holographic pattern.
4. A low solvent residue UV transfer paper, characterized in that: The invention is prepared by the method for preparing low-solvent residual UV transfer paper as claimed in any one of claims 1 to 3, comprising a back coating (1), a base paper layer (2), a water-based environmentally friendly adhesive layer (3), a dielectric layer (4), a water-based bonding coating (5), a UV transfer coating (6), and a water-based paint layer (7) containing a water-based ultraviolet absorber. A back coating layer (1), a base paper layer (2), a water-based environmentally friendly adhesive layer (3), a dielectric layer (4), a water-based bonding coating layer (5), a UV transfer coating layer (6), and a water-based paint layer (7) are sequentially composited into one body, wherein the surface of the UV transfer coating layer (6) close to the water-based bonding coating layer (5) has a micro-nano structure; The water-based paint layer (7) is made of water-based acrylic varnish and added with 5-10% of water-based ultraviolet absorber based on the total mass of the water-based acrylic varnish.
5. The low solvent residue UV transfer paper according to claim 4, characterized in that: The back coating (1) is made of acrylic emulsion with a solid content of 8-15%, a softening point of 105-120°C, an acid value of 7-10 mg KOH / g, and a dry coating amount of 0.5-0.7 g / m 2 .
6. The low solvent residue UV transfer paper according to claim 4, characterized in that: The water-based environmentally friendly adhesive layer (3) is made of water-based environmentally friendly acrylic polymer transfer glue; the transfer glue particle diameter is 0.14 microns, the solid content is 43±2%, the pH value is 5.0-7.0, the viscosity measured at a temperature of 25°C is 40-50 seconds, and the coating amount is 5-8g / m 2 .
7. The low solvent residue UV transfer paper according to claim 4, characterized in that: The dielectric layer (4) is a transparent dielectric layer or a metal dielectric layer.
8. The low solvent residue UV transfer paper according to claim 7, characterized in that: The dielectric layer (4) is a zinc sulfide dielectric layer. The zinc sulfide dielectric layer uses block zinc sulfide. The block zinc sulfide is heated at high temperature and vaporized by vacuum aluminum plating equipment, then cooled and deposited on the surface of the aqueous bonding coating (5) to form a zinc sulfide highlight layer. The transmittance represented by the thickness of the zinc sulfide is 64-66%.
9. The low solvent residue UV transfer paper according to claim 4, characterized in that: The water-based bonding coating (5) is made of water-based polyurethane, water-based acrylic resin or a mixture thereof. The solid content of the water-based bonding coating (5) is 8-15%, and the dry coating amount is 0.3-0.6 g / m 2 The thickness of the water-based binding coating (5) is 1 to 3 μm, and the surface shape of the water-based binding coating (5) is consistent with the micro-nano structure of the UV transfer coating (6).
10. The low solvent residue UV transfer paper according to claim 4, characterized in that: The UV transfer coating (6) is made of UV light-cured acrylic monomer coating, and the cross-section of the micro-nano structure on the surface of the UV transfer coating (6) is one of arc, square, triangle, trapezoid, and step shapes, or a combination thereof.
Citation Information
Patent Citations
Deep relief nano narrow molecular weight transfer material and preparation method thereof
CN111319388A
Silver color shifts card paper
CN205553469U